Reluctant Mathematician: Skills-Based MOOC Scaffolds Wide Range of Learners. Issue 1 (11th November 2015) - Lambert, Sarah
The University of Wollongong's first locally developed and hosted Massive Open Online Course (MOOC) "The Reluctant Mathematician" was run in the last four weeks of our summer holiday, prior to Autumn session in 2014. It was developed to lift maths skills at our university and also in the community – where maths skills continue to be a challenge and in some cases a source of stress. Internally the MOOC provided an alternative online way to support students who struggle with mathematics at university level, as a complement to the existing face to face small group workshops and individual consultations. This paper describes the aims, rationale of the learning design, and evaluation of the MOOC. Data sources include enrolment/demographic data, analytics data of student patterns of use, assignment submission data, and qualitative feedback via online forms. It provides some support for recent non-binary definitions of MOOCs proposed by Lane (2012 ), and discusses the importance of discipline specific issues in the design of the MOOC, such as scaffolding learning experiences to address high-stress and low self-efficacy in maths learners.